2009
DOI: 10.1111/j.1365-2486.2008.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of isoprene emission to ambient CO2 changes and implications for global budgets

Abstract: We explore the potential role of atmospheric carbon dioxide (CO 2 ) on isoprene emissions using a global coupled land-atmosphere model [Community Atmospheric Model-Community Land Model (CAM-CLM)] for recent (year 2000, 365 ppm CO 2 ) and future (year 2100, 717 ppm CO 2 ) conditions. We incorporate an empirical model of observed isoprene emissions response to both ambient CO 2 concentrations in the long-term growth environment and short-term changes in intercellular CO 2 concentrations into the MEGAN biogenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(173 citation statements)
references
References 62 publications
2
162
4
Order By: Relevance
“…Carslaw et al [3] summarize several earlier publications that show that projections of future changes in isoprene emissions from climate effects (i.e., increasing temperatures) from year 2000 to 2100 range from an increase by 20 to 55%, increasing up to 90% when dynamic vegetation is included [30]. The response to land use changes ranged in different studies from − 20 to + 30%, while a decrease of 8% was predicted in response to increasing CO 2 concentrations [31]. Monoterpene emissions were projected to increase from 20 to 60% considering the effect of changed climates [32][33][34].…”
Section: Biogenic Volatile Organic Gases and Secondary Organic Aerosolsmentioning
confidence: 99%
“…Carslaw et al [3] summarize several earlier publications that show that projections of future changes in isoprene emissions from climate effects (i.e., increasing temperatures) from year 2000 to 2100 range from an increase by 20 to 55%, increasing up to 90% when dynamic vegetation is included [30]. The response to land use changes ranged in different studies from − 20 to + 30%, while a decrease of 8% was predicted in response to increasing CO 2 concentrations [31]. Monoterpene emissions were projected to increase from 20 to 60% considering the effect of changed climates [32][33][34].…”
Section: Biogenic Volatile Organic Gases and Secondary Organic Aerosolsmentioning
confidence: 99%
“…Global modelling studies simulating future isoprene emissions have shown that including an algorithm that accounts for inhibition of the isoprene emissions from plants due to elevated CO 2 concentration can significantly diminish the predicted isoprene increase (e.g. Heald et al, 2009). However, recent studied suggest that this inhibition may not occur in warmer climate (Sun et al, 2013) and a better understanding of this process is needed.…”
Section: Co 2 Inhibition Factormentioning
confidence: 99%
“…The γ CO 2 factor is a new MEGANv2.1 model feature, which accounts for the impact of concentration of carbon dioxide (CO 2 ) on isoprene emission. Following the parameterization of Heald et al (2009), isoprene emissions decrease when ambient CO 2 concentration increases above the level of 400 ppmv (parts per million by volume). In view of the lack of clear experimental evidence of an effect, γ CO 2 is set to 1 for all other species.…”
Section: Algorithm Of the Emission Estimationmentioning
confidence: 99%
“…However, given limitations in both our measurement and understanding of BVOC emissions and SOA formation (Hallquist et al, 2009), it is unclear whether biogenic emissions, and the aerosols produced upon oxidation of these emissions, have also changed over this same time period. The evolution of these biogenic emissions is difficult to predict (e.g., Heald et al, 2009), representing a significant hurdle for future air quality management efforts and the prediction of climate forcing.…”
Section: Introductionmentioning
confidence: 99%